Analysis of Investment and Government Expenditure on Employment Opportunities in North Sumatra - Munthe, Syafaruddin (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research aims to analyze the influence of exogenous variables on endogenous variables, namely investment, government spending and employment opportunities. This type of research is quantitative analysis using secondary data with a time series from 1993 to 2022 obtained from the Central Statistics Agency (BPS) of North Sumatra and Bank Indonesia (BI). The data analysis technique in this research uses a multiple regression analysis model. The results of this research show that exogenous variables have a significant effect on endogenous variables in the equation model. The investment and government expenditure variables have a significant effect on the employment opportunity variable. For this reason, it is necessary to increase investment (PMA and PMDN) and government spending so that there is a coherent increase in economic growth. With the simultaneous increase in these two variables, it is hoped that job opportunities will expand